2020
DOI: 10.2308/tar-2018-0120
|View full text |Cite
|
Sign up to set email alerts
|

Using Audit Programs to Improve Auditor Evidence Collection

Abstract: Auditors experience difficulty auditing accounts on which it is difficult to identify in advance all the evidence necessary to perform an effective audit. These accounts are challenging because they commonly require auditors to collect additional, relevant evidence in response to new information received during evidence collection. We address this experimentally by examining whether changing the focus of audit programs from plan-focused (i.e., focused on the planned audit procedures) to goal-focused (i.e., foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Alternatively, they can bypass recognition and invoke these processes directly by priming a deliberative mindset (Griffith, Hammersley, Kadous, and Young 2015), or indirectly by priming intrinsic motivation (Kadous and Zhou 2019) or an accuracy goal (as in the current paper). Judgment frameworks that prioritize particular issues (Backof et al 2016), documentation instructions that require broad consideration of why certain outcomes could occur (Rasso 2015), and audit programs that emphasize the overall task or a balanced consideration of evidence (Austin et al 2020; Hammersley and Ricci 2020) may also encourage analytical processes with or without prompting awareness of the need for such processes.…”
Section: Frameworkmentioning
confidence: 99%
“…Alternatively, they can bypass recognition and invoke these processes directly by priming a deliberative mindset (Griffith, Hammersley, Kadous, and Young 2015), or indirectly by priming intrinsic motivation (Kadous and Zhou 2019) or an accuracy goal (as in the current paper). Judgment frameworks that prioritize particular issues (Backof et al 2016), documentation instructions that require broad consideration of why certain outcomes could occur (Rasso 2015), and audit programs that emphasize the overall task or a balanced consideration of evidence (Austin et al 2020; Hammersley and Ricci 2020) may also encourage analytical processes with or without prompting awareness of the need for such processes.…”
Section: Frameworkmentioning
confidence: 99%
“…Future research can also consider examining other situations in which innovative audit procedures could be particularly valuable, such as audits of complex estimates. Such accounts often require the collection of nonstandard evidence (Asare and Wright 2004;Griffith, Hammersley, Kadous, and Young 2015) and academics (Hammersley and Ricci 2018) as well as regulators (PCAOB 2014; CPAB 2014) have suggested that the reliance on standard step-by-step audit programs is preventing auditors from effectively responding to such demands. Future research could consider the issue of implementing innovative procedures in audit programs, as well as the effectiveness of conducting more innovative audit procedures, in overcoming this issue.…”
Section: Resultsmentioning
confidence: 99%
“…Hammersley and Ricci (2021) study whether audit programs with either a plan‐focus (i.e., focus on planned audit procedures) or a goal‐focus (i.e., focus on the task goal) affect auditors' evidence collection. Results from an experiment with 123 experienced auditors from the United States suggest that goal‐focused auditors collect more effective evidence than plan‐focused auditors and, in turn, follow up on this evidence in a way that could improve audit quality.…”
Section: Review Of the Relevant Literaturementioning
confidence: 99%